Hepatic microbiome in healthy lean and obese humans - Malte Palm Suppli; Jonatan Ising Bagger; Benjamin Lelouvier; Amandine Broha; Mia Demant; Merete Juhl Kønig; Charlotte Strandberg; Asger Lund; Tina Vilsbøll; Filip Krag Knop (JHEP Reports, 2021)
Background & Aims: Dysbiosis of the gut microbiota in response to an energy-rich Western diet and the potential leak of bacteria and/or bacterial products from the intestine to the liver is perceived as a potential risk factor for the development of non-alcoholic fatty liver disease (NAFLD). We investigated the microbiome in liver biopsies from healthy lean and obese individuals and compared it with their blood microbiome. Methods: We examined liver biopsies from 15 healthy lean and 14 obese individuals (BMI of 18.5–25 and 30–40 kg/m2, respectively). Bacterial 16S ribosomal DNA (rDNA) was analysed by quantitative polymerase chain reaction (qPCR) and 16S metagenomic sequencing targeting the hypervariable V3–V4 region. Metagenomic analysis was performed using the linear discriminant analysis effect size (LEfSe) algorithm. Data are medians with IQRs in brackets. Results: Histology revealed hepatic steatosis in 13 obese individuals and in 2 lean individuals. A robust signal from qPCR revealed significantly higher amounts of bacterial rDNA copies in liver samples from obese individuals compared with those from lean individuals (148 [118–167] vs. 77 [62–122] 16S copies/ng DNA, p <0.001). Liver biopsies from the obese group were characterised by lower alpha diversity at the phylum level (Shannon index 0.60 [0.55–0.76] vs. 0.73 [0.62–0.90], p = 0.025), and metagenomic profiling revealed a significantly higher proportion of Proteobacteria in this group (81.0% [73.0–82.4%] vs. 74.3% [68.4–78.4%], p = 0.014). Conclusions: We provide evidence for the presence of bacterial rDNA in the healthy human liver. Based on differences in the hepatic microbiome between obese individuals and healthy lean individuals, we suggest that changes in the liver microbiome could constitute an additional risk factor for the development of NAFLD. Lay summary: Non-alcoholic fatty liver disease (NAFLD) has become the most common liver disease globally, and new evidence suggests that obesity is associated with a disturbed gut bacterial composition, which may influence the development of NAFLD. We examined the composition of bacterial DNA in liver biopsies from healthy lean and obese individuals and found a different composition of bacterial DNA in liver biopsies from the obese group. We propose that the increased bacterial DNA load in the livers of obese individuals could constitute an early risk factor for the progression of NAFLD. Clinical trial number: NCT02337660